2012
DOI: 10.1158/2159-8290.cd-12-0003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of an Isoform-Selective Inhibitor of PI3K-p110β as a Potential Anticancer Agent

Abstract: Genetic approaches have demonstrated that the p110β isoform of PI3K is essential for the growth of PTEN-null tumors. Thus, it is desirable to develop p110β-specific inhibitors for cancer therapy. Using a panel of PI3K isoform-specific cellular assays, we screened a collection of compounds possessing activities against kinases in the PI3K superfamily and identified a potent and selective p110β inhibitor: KIN-193. We show that KIN-193 is efficacious specifically in blocking AKT signaling and tumor growth that ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
147
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 23 publications
10
147
0
Order By: Relevance
“…Because p110 isoform-selective inhibitors are available, and some of them are entering clinical trials (33), we sought to verify the isoform dependence shown in the genetic model using pharmacological inhibitors. For this study we used BYL719, a p110α-selective inhibitor currently in clinical trials for cancer patients (34), and KIN193, a p110β-selective inhibitor that effectively reduces PI3K signaling in some PTEN-deficient cancer cells (23).…”
Section: Pharmacological Inhibition Of P110α Effectively Blocks Tumormentioning
confidence: 99%
See 2 more Smart Citations
“…Because p110 isoform-selective inhibitors are available, and some of them are entering clinical trials (33), we sought to verify the isoform dependence shown in the genetic model using pharmacological inhibitors. For this study we used BYL719, a p110α-selective inhibitor currently in clinical trials for cancer patients (34), and KIN193, a p110β-selective inhibitor that effectively reduces PI3K signaling in some PTEN-deficient cancer cells (23).…”
Section: Pharmacological Inhibition Of P110α Effectively Blocks Tumormentioning
confidence: 99%
“…Notably, ablation of p110α alone had no effect on tumor formation in this system. It has also been reported that p110β-selective inhibitors reduce AKT phosphorylation in PTEN-null human breast cancer cell lines (23). Other groups found that specific knockdown of p110β, but not p110α, resulted in downregulation of PI3K pathway signaling and inhibition of growth in both cell-based and in vivo studies of breast and prostate human Significance Aberrant activation of the PI3K pathway is a frequent event in human cancer, making PI3K an attractive target in cancer therapy.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…64,65 Consistent with this biochemical finding, preclinical studies have shown a positive correlation between loss of PTEN and sensitivity to selective inhibitors of PI3Kβ. 66 Phase I trials of two different PI3K-selective inhibitors are currently enrolling patients (NCT01673737, NCT01458067).…”
Section: Other Targets and Novel Mutations In Cutaneous Melanomamentioning
confidence: 99%
“…Preclinical studies have indicated that the PI3Kb isoform (containing the p110b catalytic subunit) is the critical lipid kinase that drives primarily PI3K pathway activation, cell growth, and survival in PTEN-deficient tumor cells (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%